PENGARUH INTENSITAS MENGHAFAL AL QUR’AN DAN MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK MELALUI MEDIASI STRES AKADEMIK SANTRI DI PONDOK PESANTREN - Prasetya Utama Prasetya (Jurnal Kewidyaiswaraan, 2020)
This study aims to study the effect of the intensity of memorizing the Qur'an and motivation to learn about academic achievement through the academic stress of memorizing the Qur'an, Ibn Masykur Halimatussa'diyah Islamic Boarding School, Central Lombok. The type of research used is quantitative research. This type of research is based on the way of collecting and analyzing data in numerical form. The study design used was a cross sectional study. The subjects of this study were all 101 students of the Qur'an Ibnu Masykur Halimatussa'diyah Islamic Boarding School, Central Lombok. The data collection technique is done by using primary data and secondary data. The data analysis technique used the SEM PLS statistical test. The results showed that there was a significant influence between the intensity of memorizing the Qur'an on the academic stress of students with a value of p = 0.000 (p <0.05). The results of the second study showed that there was an indirect significant effect between the intensity of memorizing the Al Quran of the students and the academic achievement of the students through mediating academic stress with a value of p = 0.018 (p <0.05). The results of the third study show that there is a significant influence between academic stress on the academic achievement of students with a value of p = 0.016 (p <0.05). And the results of the fourth study indicate that there is a significant influence between learning motivation on the academic achievement of students with a value of p = 0.387 (p <0.05).